PELAKSANAAN PELAYANAN ADMINISTRASI KEPENDUDUKAN MELALUI APLIKASI ONLINE DISDUKCAPIL DI KOTA PADANG PROVINSI SUMATERA BARAT) - Aldri Frinaldi; Disa Amalia (Merwin Publisher, 2023)
The Disdukcapil application is an innovation of population administration services that has been implemented by the Population and Civil Registration Office in Padang City. This application has been in place since March 30, 2020. This application aims to improve the quality of service to the community and be able to break the chain of the spread of Covid-19. The implementation of the Disdukcapil application is strongly influenced by the community's response. However, in fact, there are still many people who are not satisfied with this innovation. Therefore, research was raised on